2006
DOI: 10.1118/1.2181290
|View full text |Cite
|
Sign up to set email alerts
|

A bench‐top megavoltage fan‐beam CT using ‐photodiode detectors. I. System description and detector characterization

Abstract: We describe the components of a bench-top megavoltage computed tomography (MVCT) scanner that uses an 80-element detector array consisting of CdWO4 scintillators coupled to photodiodes. Each CdWO4 crystal is 2.75 x 8 x 10 mm3. The detailed design of the detector array, timing control, and multiplexer are presented. The detectors show a linear response to dose (dose rate was varied by changing the source to detector distance) with a correlation coefficient (R2) nearly unity with the standard deviation of signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
60
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(62 citation statements)
references
References 57 publications
(78 reference statements)
2
60
0
Order By: Relevance
“…23 For indirect detection, some of the detectors considered include thick optical fibers detecting Cerenkov radiation, 24 2D polymer matrices filled with Gd 2 O 2 S : Tb phosphor, 25 as well as 1D and 2D crystalline scintillators ͑e.g., CsI:Tl, Bi 4 Ge 3 O 12 , CdWO 4 , and ZnWO 4 ͒, employing the concept of segmentation. [26][27][28][29][30][31][32][33][34] A series of theoretical and empirical studies has been previously reported on 2D segmented crystalline scintillators, which consists of matrices of scintillating crystals separated by septal walls to limit the lateral spread of optical photons. 25,[35][36][37][38][39][40] Monte Carlo simulations of radiation and optical transport have suggested that EPIDs employing segmented CsI:Tl and Bi 4 Ge 3 O 12 ͑BGO͒ detectors up to 40 mm thick can offer DQE values of up to 29% and 42%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…23 For indirect detection, some of the detectors considered include thick optical fibers detecting Cerenkov radiation, 24 2D polymer matrices filled with Gd 2 O 2 S : Tb phosphor, 25 as well as 1D and 2D crystalline scintillators ͑e.g., CsI:Tl, Bi 4 Ge 3 O 12 , CdWO 4 , and ZnWO 4 ͒, employing the concept of segmentation. [26][27][28][29][30][31][32][33][34] A series of theoretical and empirical studies has been previously reported on 2D segmented crystalline scintillators, which consists of matrices of scintillating crystals separated by septal walls to limit the lateral spread of optical photons. 25,[35][36][37][38][39][40] Monte Carlo simulations of radiation and optical transport have suggested that EPIDs employing segmented CsI:Tl and Bi 4 Ge 3 O 12 ͑BGO͒ detectors up to 40 mm thick can offer DQE values of up to 29% and 42%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…4 However, conventional MV AMFPIs suffer from very low x ray quantum efficiency (QE) and, as a result, very low detective quantum efficiency (∼2% and 1% at 6 MV, respectively), 5 necessitating the use of relatively high imaging doses (e.g., ∼50-200 cGy) in order to achieve soft tissue visualization using MV CBCT. 6,7 To address this challenge, various approaches for increasing the QE of MV imagers have been investigated or implemented, such as xenon gas ion chambers arranged in a fan-beam geometry, 8 and thick, segmented scintillating crystals arranged in the form of a linear array [9][10][11][12] or a 2D matrix. [13][14][15][16][17][18][19][20][21][22][23][24] In particular, the approach involving a 2D matrix of segmented scintillator elements (based on CsI:Tl, Bi 4 SiO 5 [LYSO]) has been explored both theoretically and empirically.…”
Section: Introductionmentioning
confidence: 99%
“…These detectors are based on concepts involving high pressure gas ͑e.g., xenon͒ chambers employing tungsten walls, [10][11][12] thick optical fibers detecting Cerenkov radiation, 13 thick HgI 2 photoconductors, 14 segmented phosphors based on photopolymer matrices, 15 and segmented crystalline scintillators which consist of 2D matrices ͑or 1D arrays͒ of scintillator crystals separated by optically opaque septal walls. 7,[16][17][18][19] Among these approaches, segmented crystalline scintillators offer significantly improved QE, with only limited loss in spatial resolution, and possibly no substantial increase in noise compared to conventional AMFPIs. In order to examine this strategy, 1D segmented arrays incorporating zinc tungstate ͑ZnWO 4 ͒ and cadmium tungstate ͑CdWO 4 ͒ scintillators, [17][18][19] as well as 2D segmented matrices employing bismuth germanate ͑BGO͒, thallium-doped cesium iodide ͑CsI:Tl͒ and CdWO 4 scintillators, 7,[20][21][22] have been investigated by different research groups.…”
Section: Introductionmentioning
confidence: 99%
“…7,[16][17][18][19] Among these approaches, segmented crystalline scintillators offer significantly improved QE, with only limited loss in spatial resolution, and possibly no substantial increase in noise compared to conventional AMFPIs. In order to examine this strategy, 1D segmented arrays incorporating zinc tungstate ͑ZnWO 4 ͒ and cadmium tungstate ͑CdWO 4 ͒ scintillators, [17][18][19] as well as 2D segmented matrices employing bismuth germanate ͑BGO͒, thallium-doped cesium iodide ͑CsI:Tl͒ and CdWO 4 scintillators, 7,[20][21][22] have been investigated by different research groups. Recently, a 40 mm thick segmented CsI:Tl detector, with an element-toelement pitch of 1.016 mm and an area of 16.25 ϫ 16.25 cm 2 , has been developed and evaluated by our group.…”
Section: Introductionmentioning
confidence: 99%